2022
DOI: 10.1101/2022.02.16.480671
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kinesin-1 promotes centrosome clustering and nuclear migration in theDrosophilaoocyte

Abstract: Accurate positioning of the nucleus is essential in many cellular contexts. Microtubules and their associated motors are important players in this process. Although nuclear migration in Drosophila oocytes is controlled by microtubule-generated forces, a role for microtubule-associated molecular motors in nuclear positioning has yet to be reported. In this study, we first characterize novel landmarks that allow a precise description of the pre-migratory stages. Using these newly defined stages, we report that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
(154 reference statements)
0
1
0
Order By: Relevance
“…Indeed, work in C.elegans showed that Kinesin-1 was important to prevent the precocious activation of the sperm centriole during female Meiosis ( McNally et al, 2012 ). Kinesin-1 is also important for centrosome clustering in the Drosophila oocyte, a phenotype that could be mimicked by the artificial activation of Polo at the centrosome ( Loh et al, 2022 Preprint ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, work in C.elegans showed that Kinesin-1 was important to prevent the precocious activation of the sperm centriole during female Meiosis ( McNally et al, 2012 ). Kinesin-1 is also important for centrosome clustering in the Drosophila oocyte, a phenotype that could be mimicked by the artificial activation of Polo at the centrosome ( Loh et al, 2022 Preprint ).…”
Section: Discussionmentioning
confidence: 99%